On living through Soviet Russia - Bertaux, Daniel; Thompson, Paul, 1935-; Rotkirch, Anna, 1966- (Routledge studies in memory and narrative, 2004)
This book is a fascinating collection of life stories and family history interview material collected by the editors and two Russian groups of interviewers.